2018
DOI: 10.1002/jsfa.9352
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salmon milt extracts attenuate hepatosteatosis and liver dysfunction in diet‐induced fatty liver model

Abstract: Dietary SME improved liver function in the diet-induced fatty liver model. Activation of mitochondrial biogenetic function might be involved in this process. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The study provided insights into the potential of SM DNA for developing functional foods with therapeutic effects against liver dysfunction. 11 Several other studies have also reported the efficacy of salmon milt extracts in improving alcohol-induced liver cirrhosis 12 and diet-induced fatty liver and liver dysfunction in mice 13 and increasing the activity of superoxide dismutase in the liver in an aging-accelerated mouse model. 14 In addition, in human clinical trials, administration of nucleic acid-supplemented drinks promoted alcohol metabolism and reduced blood acetaldehyde levels.…”
Section: Introductionmentioning
confidence: 98%
“…The study provided insights into the potential of SM DNA for developing functional foods with therapeutic effects against liver dysfunction. 11 Several other studies have also reported the efficacy of salmon milt extracts in improving alcohol-induced liver cirrhosis 12 and diet-induced fatty liver and liver dysfunction in mice 13 and increasing the activity of superoxide dismutase in the liver in an aging-accelerated mouse model. 14 In addition, in human clinical trials, administration of nucleic acid-supplemented drinks promoted alcohol metabolism and reduced blood acetaldehyde levels.…”
Section: Introductionmentioning
confidence: 98%
“…We also reported that mitochondrial dysfunction could be caused by the low levels of several proteins involved in mitochondrial biogenesis, such as peroxisome proliferator‐activated receptor gamma co‐activator 1 alpha, mitochondrial thioredoxin, cardiolipin synthase, peroxisome proliferator‐activated receptor alpha, 11 indicating that reduction in CL level and mitochondrial dysfunction could be directly related. Cardiolipin is localized only in the mitochondrial cristae, and is strongly associated with regulating mitochondrial function 19 .…”
Section: Discussionmentioning
confidence: 86%
“…All animal experimental protocols were approved by the animal care committee of Hokkaido University (approval protocol number: 15–0174) as explained in a previous study 11 . In this study, we used the same liver samples as those reported in a previous study 11 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations